The making of modern Japan - Jansen, Marius B. (The belknap Press, 2000)
Japan's society has shown enormous resilience and strength in the past millennium. A thousand years ago the court society of lady Murasaki's Tale of Genji was giving way to that of warriors whose rule was fastened on the country for eight hundred years. The Meiji revolution disarmed those samurai and armed the state instead. The new Meiji empire flourished briefly, but in defeat that state was itself disarmed. Reconstruction brought enormous economic influence and power, but that structure too was not immune to cyclical decline.